2016
DOI: 10.1142/s0219455415500431
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Foundation Type on Seismic Performance of Buildings Considering Soil–Structure Interaction

Abstract: In selecting the type of foundation best suited for mid-rise buildings in high risk seismic zones, design engineers may consider that a shallow foundation, a pile foundation, or a pile-raft foundation can best carry the static and dynamic loads. However, di®erent types of foundations behave di®erently during earthquakes, depending on the soil-structure interaction (SSI) where the properties of the in situ soil and type of foundation change the dynamic characteristics (natural frequency and damping) of the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…It has been reported that the structure supported by deep foundation experiences less storey drifts in comparison to the structure supported by the shallow foundation due to the reduced rocking components [43,44]. They concluded that the choice of foundation type is dominant and should be included while investigating the in uence of soil-structure interaction on the performance of mid-rise buildings sitting in soft soil.…”
Section: Storey Driftmentioning
confidence: 99%
“…It has been reported that the structure supported by deep foundation experiences less storey drifts in comparison to the structure supported by the shallow foundation due to the reduced rocking components [43,44]. They concluded that the choice of foundation type is dominant and should be included while investigating the in uence of soil-structure interaction on the performance of mid-rise buildings sitting in soft soil.…”
Section: Storey Driftmentioning
confidence: 99%
“…It was determined that the seismic resistance (rotational inertia) increased in a square relationship with an increase in the plane size R ( R denotes the radial distance from the centre of gravity and one rotation corner at the bottom of the structure in a plane), whereas the seismic demand (the overturning moment) increased linearly with the plane size R. Therefore, as long as a high‐rise structure's plane size R was large enough, the structure could theoretically survive any earthquake and remain stable. In addition to reducing the seismic response by eliminating the connection between the superstructure and foundation, some scholars have proposed using the failure of the soil to form the rocking structure, and the impacts of the soil–foundation interaction on the seismic response characteristics of the rocking structure have been studied …”
Section: Introductionmentioning
confidence: 99%
“…Chu and Truman [15] studied the effects of pile spacing on soil-structure interaction and noted that although largely spaced pile groups have slightly larger pile head responses than closely spaced pile groups, the general effects of the pile spacing ratio on the seismic response of soil-pile systems are insignificant. Hokmabadi and Fatahi [16] concluded that the influence of the foundation type on building seismic performance is a major contributor to building seismic response with SPSI and therefore should be given careful consideration. Van Nguyen et al [17] analyzed the influence of pile size and load-bearing mechanism on the seismic performance of buildings and showed that the type and size of the piles influence the dynamic characteristics and seismic response of the building due to interaction between the soil, piled raft, and structure.…”
Section: Introductionmentioning
confidence: 99%